2017
DOI: 10.1007/978-3-319-46709-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Protocols: Options, Approaches, Implementation, Benefits

Abstract: Monitoring and adaptive management are fundamental concepts to rangeland management across land management agencies and embodied as best management practices for private landowners. Historically, rangeland monitoring was limited to determining impacts or maximizing the potential of specific land uses-typically grazing. Over the past several decades, though, the uses of and disturbances to rangelands have increased dramatically against a backdrop of global climate change that adds uncertainty to predictions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…For this study, MSC was defined as a key forest indicator primarily because of its relevance, for being informative over large regions (Karl et al 2017), but also because of the large number of countries with available information to estimate it. The proposed shrub indicator, MSC, can be estimated for species from NFI data for all except three of the countries that assess shrub cover.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, MSC was defined as a key forest indicator primarily because of its relevance, for being informative over large regions (Karl et al 2017), but also because of the large number of countries with available information to estimate it. The proposed shrub indicator, MSC, can be estimated for species from NFI data for all except three of the countries that assess shrub cover.…”
Section: Discussionmentioning
confidence: 99%
“…Although the HAF method most closely matches the maximum height measurements from previous sage‐grouse habitat studies (see Connelly et al ), there is value in coordinating methods with other monitoring efforts (Karl et al ). The AIM monitoring methods are widely applied across BLM lands and also used by the NRCS National Resources Inventory, National Park Service, and other land management organizations.…”
Section: Discussionmentioning
confidence: 72%
“…When using remotely sensed data, the subject of "ground truthing" is often a consideration. It is common practice to collect ground-based transect data to compare with remote sensing-based vegetation cover estimates, and numerous studies have found approximate equivalence between plant canopy cover measured on the ground and that measured in image data [44,[52][53][54]. In contrast, some studies showed the image-assessed canopy to be substantially different from the ground-assessed canopy [55,56].…”
Section: Comparison Of Map Validation Methodsmentioning
confidence: 99%